Response of Weaner Pigs to Graded Levels of Sickle Pod (Senna obtusifolia) Leaf Meal in Diets (British Journal of Multidisciplinary and Advanced Studies, 2023)
The experiment was carried out at Bajabure Federal Housing Estate Phase three, Girei Local Government Area of Adamawa State, Nigeria. Twelve (12) weeks feeding trial was conducted to evaluate the effects of feeding Senna obtusifolia leaf meal on the growth performance, of weaner pigs.   Five experimental diets were formulated using Senna obtusifolia leaf meals at 0%, 15%, 20%, 25% and 30%. The diets were coded T1, T2, T3, T4 and T5 respectively. Twenty (50) weaner pigs were randomly assigned to the five experimental diets in a completely randomized design (CRD). Each treatment group was replicated five times with two pigs per replicate. Parameter measured were lived weight, average daily feed intake (ADFI), average daily weight gain (ADWG), feed conversion ratio (FRC) The growth performance showed significant (p˂0.05) differences. The ADFI, AFWG, ATWG, ATFI, ADWG and FRC, all showed no significant difference (p˃0.05) across the treatments. The pigs were fed at 4% bodyweight for twelve (12) weeks. The proximate composition of Senna obtusifolia showed it contains 93.32% dry matter, 25.37% crude protein, 25.37%, crude fibre, 12.16% ash, 4.07% ether extract and 38.14% nitrogen free extract. But T4 and T5 are recommended because of good health states, growth rate at the end of the experiment.